Lack of Protection for Whistleblowers at the Workplace in Nigeria: Drawing Lessons from Selected Jurisdictions - David Tarh-Akong Eyongndi; Faith Nwayemogho Opara (Faculty of Law, Universitas Padjadjaran, 2022)
The Nigerian government has created anti-corruption agencies, such as the Economic and Financial Crimes Commission and the Independent Corrupt Practices and other related offences Commission (ICPC), to contend with corruption. In 2015, the Federal Ministry of Finance introduced the whistleblowing policy. The policy enables corrupt practices in any workplace, either private or public, to be exposed. However, following the policy, there is no legal framework for the implementation nor protection of the whistleblower. This article adopts doctrinal and comparative methodology to examine the utilitarian values and the propriety of whistleblowing vis-à-vis the employee’s obligation to act in good faith under Nigeria’s labor jurisprudence. It relies on primary and secondary data. It discusses the challenges confronting whistleblowing at the workplace in Nigeria. It also examines the practice in Britain, India, South Africa, and Ghana to be compared with Nigeria. It reveals that whistleblowing is an effective tool to combat corruption/malpractices in the workplace. Unlike in Britain, India, South Africa, and Ghana, there is no specific legislation on whistleblowing in Nigeria. It recommends awareness on the need of Nigerians’ active participation in whistleblowing and enactment of a subject-specific law to protect whistleblowing and whistleblowers as in ones in Britain, India, South Africa, and Ghana.DOI: https://doi.org/10.22304/pjih.v9n3.a7